Geografia e saúde: o que está em jogo? História, temas e desafios - Christovam Barcellos; Gustavo D. Buzai; Pascal Handschumacher (Confins)
This article seeks to recover the origins of health geography, from the production of the first disease maps to the incorporation of new spatial analysis techniques in the last decades. This evolution has also been accompanied by a profound review of paradigms, theories and methods, with a greater emphasis on the relationship between man and the environment, and with approaches that relate socio-spatial structure to health problems at the various scales where they manifest themselves. The current health geography is confronted with the need to articulate the association between the health-disease process and the disease-care binomial, in search of equity, prevention of diseases and diseases and health promotion.